The evolution, challenges and prospects of implementing Massive Open Online Courses (MOOCs) in Malaysian public universities / Ibhrahim Zakaria ... [et al.] - Zakaria, Ibhrahim; Anual, Norazlan; Abdul Karim, Zatul Himmah; Mohd Firdaus Kozako, Intan Nurul'ain; Zamri, Muhammad Nasrullah (UiTM Press, 2024)
Massive Open Online Courses (MOOCs) have emerged as a promising educational innovation, aiming to democratize access to quality education on a global scale. In the context of Malaysian public universities, MOOCs have garnered significant interest in enhancing educational outreach, improving learning outcomes, and fostering lifelong learning opportunities. However, the implementation of MOOCs in this setting faces several challenges that impact their effectiveness and long-term sustainability. This review was written based on a careful analysis of the published MOOC literature (2008-2023) identified through journals, database searches, searching the Web, and chaining from known sources to form the base for this review. The review intends to understand how the evolution of MOOCs affects the prospects of MOOCs and how universities incorporate MOOCs into their educational frameworks. In addition, this paper aims to explore the current and anticipated future challenges that hinder the successful integration of MOOCs especially in public universities across Malaysia. The key challenges identified in the present implementation include limited faculty buy-in and engagement, lack of appropriate technological infrastructure, concerns over course quality and accreditation, and difficulties in assessing and recognizing learners' achievements. Additionally, issues related to cultural barriers and language diversity within the Malaysian context are also found to influence the effective utilization of MOOCs. Looking into the future, this paper will also explore additional potential challenges that may arise in the continued implementation of MOOCs in public universities in Malaysia. Anticipated challenges include evolving pedagogical practices, ensuring equitable access for all learners, addressing the digital divide, and keeping pace with rapidly advancing technology. By shedding light on the current and future challenges faced by public universities in Malaysia in implementing MOOCs, this research aims to provide valuable insights for policymakers, administrators, and educators to enhance the efficacy of MOOCs and leverage their potential for advancing education in the country. Recommendations stemming from this research may include faculty training and development, investment in technological infrastructure, fostering collaborations with private sectors, and designing inclusive and culturally sensitive learning environments. Ultimately, understanding and addressing these challenges are crucial to ensuring the successful integration of MOOCs within the Malaysian higher education landscape, contributing to the nation's efforts to provide accessible, high-quality education to a diverse and aspiring population.